2013
DOI: 10.1161/hypertensionaha.113.02250
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Endostatin, Hypertension Duration, and Hypertensive Target-Organ Damage

Abstract: Abstract-Our aim is to study associations between circulating endostatin, hypertension duration, and hypertensive target-organ damage. Long-term hypertension induces cardiovascular and renal remodeling. Circulating endostatin, a biologically active derivate of collagen XVIII, has been suggested to be a relevant marker for extracellular matrix turnover and remodeling in various diseases. However, the role of endostatin in hypertension and hypertensive targetorgan damage is unclear. Serum endostatin was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 52 publications
3
38
1
Order By: Relevance
“…The endostatin levels were about five-fold higher in the present study as compared with elderly individuals in the general population [28], which may partly be explained by the fact that endostatin has been shown to be associated with many risk factors that are highly prevalent in HD patients: gluco-metabolic disturbance [31,32], elevated blood lipids [33], and long term hypertension [28]. The high levels may in HD patients may additionally be explained by the fact that urinary excretion is the major elimination route of endostatin [34].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…The endostatin levels were about five-fold higher in the present study as compared with elderly individuals in the general population [28], which may partly be explained by the fact that endostatin has been shown to be associated with many risk factors that are highly prevalent in HD patients: gluco-metabolic disturbance [31,32], elevated blood lipids [33], and long term hypertension [28]. The high levels may in HD patients may additionally be explained by the fact that urinary excretion is the major elimination route of endostatin [34].…”
Section: Discussioncontrasting
confidence: 53%
“…Elevated endostatin levels have been suggested as a biomarker of a rapid turnover of the extracellular matrix in patients with malignant diseases, such as renal carcinoma [27], and in patients with hypertensive renal disease [28]. Yet, initiated extra cellular matrix remodeling has been shown to be present already in early CKD stages [10,27,29], and may thus progress further during HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet to date, reports on the role of collagen XVIII and endostatin in the development of renal impairment from community-based surveys are limited. We recently reported that serum endostatin was associated with the urinary albumin/creatinine ratio in elderly individuals with hypertension, suggesting that endostatin may be a biomarker of, or causally involved, in the pathophysiology of hypertensive kidney damage [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Especially, the elderly appeared to have high serum endostatin levels in the absence of CRC. The mechanism of such age-related increase in endostatin levels is unknown, but it might be associated with age-related increase in cardiovascular disease and the elevated endostatin levels in these patients (Mitsuma et al, 2007;Carlsson et al, 2013). Li et al, 2012 have reported that increased serum endostatin levels correlate with CRC progression.…”
Section: Discussionmentioning
confidence: 99%